Emphysematous Prostatic Abscess Due to Candidiasis: A Case Report - Yung-Shun Juan; Chun-Hsiung Huang; Ko Chang; Chii-Jye Wang; Shu-Mien Chuang; Jung-Tsung Shen; Wen-Jeng Wu (Kaohsiung Journal of Medical Sciences, 2008)
Prostatic abscess is an uncommon condition and clinical diagnosis is difficult. The classical symptoms and signs of prostatic abscess are variable and nonspecific. Here, we report a rare case of emphysematous prostatic abscess due to candidiasis in a 68-year-old man with diabetes and liver cirrhosis. The diagnosis was confirmed by pelvic computed tomography (CT) and successfully treated by antibiotics and CT-guided percutaneous abscess drainage. This case highlights the importance of early and accurate diagnosis of emphysematous prostatic abscess followed by appropriate treatment.